Simulation and Modeling of Silicon Based Single Electron Transistor - Malik Ashter Mehdy; Mariagrazia Graziano; Gianluca Piccinini (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this work, we simulated and modeled silicon quantum dot based single electron transistor (SET). We simulated the device using non-equilibrium Green’s function (NEGF) formalism in transport direction coupled with Schrodinger equation in transverse directions. The characteristics of SET such as Coulomb blockade and Coulomb diamonds were observed. We also present a new efficient model to calculate the current voltage (IV) characteristics of the SET. The IV characteristic achieved from the model are very similar to those from simulations both in shape and magnitude. The proposed model is capable of reproducing the Coulomb diamond diagram in good agreement with the simulations. The model, which is based on transmission spectrum, is simple, efficient and provides insights on the physics of the device. The transmission spectrum at equilibrium is achieved from simulations and given as input to the model. The model then calculates the evolved transmission spectra at non-equilibrium conditions and evaluates the current using Landauers formula.